Performance Enhancement of Routing Protocols in Mobile Wireless Ad-Hoc Networks Using Fuzzy Reasoning Algorithm - Natsheh, Essam Fathi (2006)
The challenge in creating a routing protocol for ad-hoc networks is to design a single protocol that can adapt to the wide variety of conditions that can be present in any ad-hoc network enviroment. The routing protocol must perform efficiently in enviroments in which it suffers from high nodes mobility and many wireless transmission constraints. Because it it often impossible to know what enviroment the protocol will find itself in, and because the enviroment can change unpredictably, the routing protocol must be able to adapt automatically. In this thesis, we use a fuzzy reasoning algorithm (FRA) as a highly adaptive algorithm to achieve that goal. We will present the various application of that algorithm to ad-hoc routing protocols. Then, we will focus on four major applications that are the core of any ad-hoc routing protocol. These applications are: route lifetime estimation, local connectivity management, nodes affinity management, and active queue management. In the first method, the fuzzy reasoning is used to estimate the time route can stay active in the routing table. In the second method, fuzzy reasoning is used to optimize the maximum time period that can transpire before the node broadcast the ‘Hello” messages. Mapping the relationship between the signal strength fluctuation and links lifetime is presented in the third method. Finally, in the last method fuzzy reasoning is used for network congestion estimation and estimating time to start dropping incoming packets. Extensive performance analysis via simulation proves the effectiveness of using the FRA to improve the accuracy of routing protocol parameters and hence the overall network performance.